Development and validation of diffusion-controlled model for predicting polycyclic aromatic hydrocarbons from baking-free brick derived from oil - based drilling cuttings. (1st January 2023) - Yang, Haoyue; Wang, Zhichao; Huang, Zechun; He, Jie; Liu, Zewei; Chen, Yu; Tian, Lu; Huang, Qifei; Liu, Tingting
Abstract: Investigating the release of organic pollutants from bricks made from solid waste is essential. Based on Fick's laws of diffusion, the diffusion model and diffusion-degradation model of polycyclic aromatic hydrocarbon (PAH) emission from the bricks were deduced. The degradation and 64-day emission of PAHs in solid bricks made of oil-based drill cuttings were observed experimentally. The emission and degradation characteristics of 14 PAHs were obtained and fitted with the diffusion and diffusion-degradation models. The emission of most of the PAHs from the bricks at the beginning was in good agreement with the diffusion model, except for benzo[a]anthracene, pyrene, benzo[b]fluoranthene, benzo[k]fluoranthene, and benzo[a]pyrene. However, the emission of PAHs after some time was significantly lower than the theoretical value of the diffusion model. Moreover, fitting with the diffusion-degradation model gave better results, indicating that a joint diffusion-degradation mechanism controlled the emission of PAHs. Therefore, the diffusion-degradation model can better predict the long-term emission of PAHs in bricks made of oil-based drill cuttings. Graphical abstract: Image 1 Highlights: New diffusion model and diffusion-degradation model were proposed. Release characteristic of PAHs from OBDC brick was obtained. Diffusion and Diffusion-Degradation Model were validated based on release data. Modified prediction model for PAH release in building block materials was proposed.